1999
DOI: 10.1046/j.1365-2141.1999.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative analysis of residual disease in patients treated for adult T‐cell leukaemia/lymphoma (ATLL)

Abstract: Summary. Many adult T-cell leukaemia/lymphoma (ATLL)patients who respond to induction treatment, then relapse. Knowing the clonality pattern of residual tumourous clones during treatment could help understand disease evolution and aid therapeutic decisions. We developed a sensitive and semi-quantitative molecular analysis of these clones in ATLL patients. DNA samples from PBMCs derived from eight ATLL patients were studied over time by quadruplicate linker mediated PCR (LMPCR) amplification of HTLV-1 integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Other investigators have demonstrated that persistence of tumor clones in ATLL patients invariably correlated with disease relapse. 73 These data indicate that AZT and IFN-␣ is a suppressive rather than a curative regimen; patients in clinical remission should remain on this therapy long term. Recently, a number of ATLL patients have been reported to be in continuous remission after allogeneic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 96%
“…Other investigators have demonstrated that persistence of tumor clones in ATLL patients invariably correlated with disease relapse. 73 These data indicate that AZT and IFN-␣ is a suppressive rather than a curative regimen; patients in clinical remission should remain on this therapy long term. Recently, a number of ATLL patients have been reported to be in continuous remission after allogeneic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 96%
“…As detailed above, suppressing the anti-HTLV-1 cellular immune response contributes to the development of ATLL, whereas restoring it might have a curative effect in animal models, 98 as in humans. 56 How could somatic mutations help an infected cell escape CTL response? The generation of Tax escape mutants is the first explanation that comes to mind.…”
Section: Discussionmentioning
confidence: 99%
“…This persistence was invariably correlated with relapse and/or poor outcome. 56 A fluctuating frequency of some tumor clones was observed, with evidence for clonal change under treatment in one patient, indicating that treatment of ATLL can result in the selection of resistant clones. Finally, allogeneic bone marrow transplantation (BMT) using an HTLV-1-infected sibling as donor was found to be associated with the long-lasting disappearance of tumor clones and a possible cure of the disease.…”
Section: Figurementioning
confidence: 96%
“…LMPCR and run-o were performed as already described (Cavrois et al, 1995;1996a,b, 1998Leclercq et al, 1998Leclercq et al, , 1999. Brie¯y, DNA was digested with NlaIII in 16NlaIII bu er for 3 h at 378C.…”
Section: Samplesmentioning
confidence: 99%